Halal Supply Chain Strategy for Etawa Goat Milk to Increase Sales Volume in Senduro Lumajang Village - Lailatul Hikmah; Moch. Chotib; Misbahul Munir (Syntax Corporation Indonesia, 2023)
This research aims to identify and analyze halal supply chain strategies that can increase the sales volume of Etawa goat milk in Senduro Village, Lumajang. Etawa goat milk is a product with significant potential in the local market, especially due to the increasing demand for halal products. This research employs a qualitative descriptive analysis method to gather data on market characteristics, production processes, distribution, and challenges faced by Etawa goat milk producers. Additionally, the research involves interviews with stakeholders in the supply chain. The findings of this research identify several strategies that can be implemented to increase the sales volume of Etawa goat milk in Senduro Village, Lumajang. These strategies include improving product quality, obtaining halal certification, enhancing distribution efficiency, and improving marketing efforts. The implementation of these strategies is expected to provide significant economic benefits to Etawa goat milk producers and contribute positively to the local community's economic development. This research can serve as a guide for Etawa goat milk producers and other stakeholders in developing a more effective and sustainable supply chain in an environment that prioritizes halal aspects.